2014
DOI: 10.1111/trf.12813
|View full text |Cite
|
Sign up to set email alerts
|

Plerixafor is effective given either preemptively or as a rescue strategy in poor stem cell mobilizing patients with multiple myeloma

Abstract: BACKGROUND:Harvest of more than one CD34+ stem cell transplant has become the standard, to ensure the option for a second autologous transplantation in patients with relapsed or progressive multiple myeloma (MM). Additional administration of the CXCR-4 inhibitor plerixafor has been shown to increase the efficiency of CD34+ stem cell harvest. However, the algorithm when to apply plerixafor is still under debate. STUDY DESIGN AND METHODS:In this retrospective study, 46 MM patients were categorized into four grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 42 publications
(64 reference statements)
1
44
0
Order By: Relevance
“…This recommendation is supported by seven nonrandomized studies that reported a variety of outcomes, including number of stem cells collected and number of days of apheresis 10,11,13,15,16,24,27 . In general, those studies detected that a better mobilization response is achieved in patients failing their first mobilization attempt when plerixafor is added to their existing mobilization regimens.…”
Section: Recommendationmentioning
confidence: 69%
See 4 more Smart Citations
“…This recommendation is supported by seven nonrandomized studies that reported a variety of outcomes, including number of stem cells collected and number of days of apheresis 10,11,13,15,16,24,27 . In general, those studies detected that a better mobilization response is achieved in patients failing their first mobilization attempt when plerixafor is added to their existing mobilization regimens.…”
Section: Recommendationmentioning
confidence: 69%
“…The study by Hundemer et al 10 , in which data were matched with a historical control group on the basis of poor stemcell yield in the first apheresis session, reported a median CD34+ collection of 4.9 in 2 apheresis procedures with plerixafor and 3.7 in 4 apheresis procedures with g-csf (p = 0.01). The comparative study reported by Cheng et al 13 reported a median CD34+ collection of 8.5 for patients receiving plerixafor compared with 4.8 for patients not receiving plerixafor (p = 0.003), but the median number of apheresis procedures was not reported. Three single-arm studies 16,24,27 reported median numbers of CD34+ cells of 2.9, 5.08, and 3.42 with a median number of apheresis procedures of 1 (range: 1-3), 5 (range: 1-10), and 2 (range: 1-4) respectively.…”
Section: Peripheral Blood Cd34+ Cell Count and Number Of Apheresis Prmentioning
confidence: 95%
See 3 more Smart Citations